1993
DOI: 10.1159/000139866
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of a Bulk Laxative Containing Senna versus Lactulose in the Treatment of Chronic Constipation in Geriatric Patients

Abstract: Thirty geriatric long-stay patients aged 65-94 years (mean 81.8) participated in the trial the aim of which was to examine bulk laxative plus senna (Agiolax®) in the treatment of chronic constipation using lactulose (Levolac®) as a reference medicine. Bulk laxative plus senna (daily dosis 14.8 g) produced more frequent (p < 0.05) bowel habits (4.5 vs. 2.2-1.9/week) than lactulose (daily dosis 20.1 g). Both laxatives proved to be safe to use. Our study indicated bulk laxative plus senna to be more efficient in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
5

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 5 publications
0
39
0
5
Order By: Relevance
“…Two trials showed bulk in combination with senna was superior to lactulose. 55,56 Other direct comparisons between different laxatives or laxatives and fiber were inconclusive because of the limited number of studies, small sample sizes, or methodologic flaws. There were no definitive data that suggested fiber increased frequency more than laxatives or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Two trials showed bulk in combination with senna was superior to lactulose. 55,56 Other direct comparisons between different laxatives or laxatives and fiber were inconclusive because of the limited number of studies, small sample sizes, or methodologic flaws. There were no definitive data that suggested fiber increased frequency more than laxatives or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…132,138,139 A senna-fiber combination was more effective than lactulose in treating constipation in geriatric long-stay patients. 116,140 A meta-analysis found that stimulant laxatives provided superior efficacy for chronic idiopathic constipation (relative risk, 0.54; 95% confidence interval [CI], 0.42-0.69). The number needed to treat with stimulant laxatives was 3 (95% CI, 2.0-3.5).…”
mentioning
confidence: 99%
“…In the present study, improvement in the frequency of bowel movements and stool form was better than that observed in previous studies done on Isabgol , lactulose, Senna, and combination of “ Isabgol and senna.”[14202225] This superiority in the outcomes of the present study over previous clinical studies done on Senna alone or in combination with Isabgol husk can be due the addition of Triphala to the combination of “ Isabgol and senna.” Triphala is prepared by mixing equal parts of Emblica officinalis ( Amalaki ), Terminalia belerica ( Bibhitak ), and Terminalia chebula ( Haritaki ). It is taken in powder form in dosages of 3 to 6 g daily for the treatment of flatulence and constipation.…”
Section: Discussionmentioning
confidence: 64%